Seasons writing and environmental ethics in Nils Holgerssons underbara resa genom Sverige - Camille Deschamps Vierø (Barnelitterært Forskningstidsskrift)
This paper focuses on the meanings and functions of the seasons in Selma Lagerlöf’s Nils Holgerssons underbara resa genom Sverige (Nils Holgersson’s Wonderful Journey through Sweden) in view of environmental ethics. By concentrating on the narratology and the ecocritical issues of the classic, it questions how the attention to temporality, and more particularly to the seasons, allows for the emergence of an environmental and land ethic. It shows how the seasons are the means for the expression of all forms of life and their interconnectedness. By reading the embeddedness and the many meanings of the seasons and seasonal patterns in Nils Holgersson, this article also demonstrates the implementation of sustainable development through mutuality and reciprocity between humans and nature.